2024
DOI: 10.1101/2024.01.05.574446
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of Novel Biomarkers for Alzheimer’s Disease and Related Dementias Using Unbiased Plasma Proteomics

Benjamin Lacar,
Shadi Ferdosi,
Amir Alavi
et al.

Abstract: Alzheimer′s disease (AD) and related dementias (ADRD) is a complex disease with multiple pathophysiological drivers that determine clinical symptomology and disease progression. These diseases develop insidiously over time, through many pathways and disease mechanisms and continue to have a huge societal impact for affected individuals and their families. While emerging blood-based biomarkers, such as plasma p-tau181 and p-tau217, accurately detect Alzheimer neuropthology and are associated with faster cogniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Our study leverages a novel nanoparticle-based untargeted LC-MS/MS workflow, which has shown exceptional capacity for in-depth plasma protein coverage, quantitative performance, and analysis throughput 8,[13][14][15][16] . Here, we applied this workflow to assess the proteomic changes in a cohort of 12 volunteers following two doses of the Pfizer-BioNTech mRNA COVID-19 vaccine.…”
Section: Introductionmentioning
confidence: 99%
“…Our study leverages a novel nanoparticle-based untargeted LC-MS/MS workflow, which has shown exceptional capacity for in-depth plasma protein coverage, quantitative performance, and analysis throughput 8,[13][14][15][16] . Here, we applied this workflow to assess the proteomic changes in a cohort of 12 volunteers following two doses of the Pfizer-BioNTech mRNA COVID-19 vaccine.…”
Section: Introductionmentioning
confidence: 99%